Determination of Employee Performance: Analysis of Leadership, Competence, and Discipline through Employee Retention - Sismiati Sismiati; Syarifuddin Sulaiman; Andi Muhammad Rudhan; Nurlela Nurlela; Yosef Dema; Iwan Darmawansyah; Rizal Rahmawan; Hageem Che-Ni (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
This literature review aims to develop hypotheses for future research regarding the factors that influence employee performance in the public sector. The article, titled